Prevalence of Osteoporosis in Male Patients with Chronic Obstructive Pulmonary Disease (Medicine Today, 2018)
Osteoporosis is one of the systemic features of COPD. Aims and objective is to determine the prevalence of osteoporosis in male COPD. In a cross-sectional study, we conducted dual-energy X-ray absorptiometry bone mineral density scans of the femoral neck and lumbar spine and collected data on smoking, duration of COPD, inhaled and oral corticosteroid treatment and staging by pulmonary function tests. We included 60 male patients with COPD, the mean age was 62.4 ± 8.1 years, smoking was 36.8 ± 17.2 smoking-pack year, duration of COPD was 5.4 ± 3.3 years, GOLD stage-III (56.7%) stage-IV (38.3%) and stage-II (5.0%), use of oral steroid (11.7%) inhaled steroid (63.3%) and none (25.0%). Normal bone mineral density was in 6 (10.0%), osteopenia in 24 (40.0%) and osteoporosis in 30 (50%) patients in femoral neck; whereas normal bone mineral density was in 4 (6.7%), osteopenia in 17 (28.3%) and osteoporosis in 39 (65.0%) patients in lumbar spine. Osteoporosis is highly prevalent in male COPD patients in both femoral neck and lumbar spine.Medicine Today 2018 Vol.30(1): 1-4